Neuromuscular monitoring in clinical practice and research Mit elnem Geleitwort von Robert Jütte - Fuchs-Buder, Thomas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Neuromuscular monitoring is critical for the judicious use of muscle relaxants. In combination with reversal, it is fundamental to every successful strategy for managing postoperative residual blocks. This reference work is a compendium of all the essential information needed to monitor neuromuscular function. Physiological and pharmacological basics of neuromuscular transmission, principles of neuromuscular monitoring: How to place stimulation electrodes, properly select the stimulation mode and interprete findings, practical techniques for clinical routine, clinical concepts behind qualitative and quantitative nerve stimulators, comprehensive presentation of acceleromyography including a question & answer section, summaries of all key points, current guidelines on the scientific use of acceleromyography.
1 Principles of neuromuscular transmission -- 2 Principles of neuromuscular monitoring -- 3 Clinical application -- 4 Acceleromyography.
Keywords: Medicine; Anesthesiology; Medicine & Public Health; Anesthesiology